2019
DOI: 10.1186/s12958-019-0545-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of endometrial thickness change after progesterone administration on pregnancy outcome in patients transferred with single frozen-thawed blastocyst

Abstract: BackgroundThe aim of this study was to explore the impact of endometrial thickness change after progesterone administration on pregnancy outcome in patients transferred with single frozen-thawed blastocyst.MethodsThis observational cohort study included a total of 3091 patients undergoing their first frozen-thawed embryo transfer (FET) cycles between April 2015 to March 2019. Endometrial thickness was measured by trans-vaginal ultrasound twice for each patient: on day of progesterone administration, and on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 14 publications
4
44
1
3
Order By: Relevance
“…Our indings might be agreed with (Bu et al, 2019;Riestenberg et al, 2020) results who found no beneit from endometrial compaction on increasing pregnancy rates in FET cycles. In contrast (Haas et al, 2019;Zilberberg et al, 2020) con irmed a signi icant link between EMT compaction and Ong PR, where an increasing percentage of compaction could improve Ong PR.…”
Section: Resultssupporting
confidence: 92%
“…Our indings might be agreed with (Bu et al, 2019;Riestenberg et al, 2020) results who found no beneit from endometrial compaction on increasing pregnancy rates in FET cycles. In contrast (Haas et al, 2019;Zilberberg et al, 2020) con irmed a signi icant link between EMT compaction and Ong PR, where an increasing percentage of compaction could improve Ong PR.…”
Section: Resultssupporting
confidence: 92%
“…AMH is also an independent predictor of live birth outcome [31,32]. In addition, some studies reported that increased endometrial thickness is associated with better pregnancy outcome [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in VEGF in turn regulates the angiogenesis of the endometrium and stimulates further growth of the endometrium [9]. In a single-center retrospective control study, Zhiqin Bu found that an increased endometrial thickness after progesterone administration was associated with better pregnancy outcomes for thawed blastocyst cycles [10]. The possible reason for this con icting result is that all of our research objects were cleavage-stage embryo transfer, with the transfer period being in the early luteal phase, in contrast to that of the blastocyst transfer, which is closer to the middle luteal phase.…”
Section: Discussionmentioning
confidence: 99%